Lentivirus-mediated knockdown of P27RF-Rho inhibits hepatocellular carcinoma cell growth - Xie, Shuli; Wang, Guangyi; Chen, Guofu; Zhu, Mingguang; Lv, Guoyue (Contemporary Oncology/Współczesna Onkologia, 2017)
Aim of the study: To investigate the effects of P27RF-Rho on hepatocellular carcinoma (HCC) cell growth and explore the possibility of using it as a novel therapeutic target for liver cancer treatment. Material and methods : P27RF-Rho in HCC cells was silenced by lentivirus-mediated RNA interference, and the silencing effect was verified by RT-PCR. Cell proliferation was determined by MTT and clone formation assay. Cell cycle phase and apoptosis were detected through FACS. The expression level of cell growth, apoptosis, and metastasis associated genes was detected by quantitative PCR. Results : Lentivirus-mediated P27RF-Rho knockdown inhibited HCC cell growth and clone formation. P27RF-Rho silence induced cell cycle arrest and apoptosis. The mRNA level of genes associated with cell cycle, apoptosis, and invasion also significantly altered after P27RF-Rho knockdown. Cyclin A, CDK2, BCL-2, and MMP-9 were down-regulated. P27 and Bax were up-regulated. Conclusions : P27RF-Rho knockdown inhibits HCC cell growth, and P27RF-Rho is probably a promising target for HCC treatment.